Supervisory Leadership and Subordinate Burnout - Seltzer, Joseph; Numerof, Rita E. (Academy of Management Journal, 1988)
The article presents information on a study which investigated how the leadership behavior of a large number of supervisors, as measured by consideration and initiating structure scales, was related to their subordinates' reported burnout. Details related to the study's methods and results for hierarchical regression analysis of burnout are presented. The author provides an analysis of variance for subordinate burnout. A discussion is presented about the effects of leadership on employee morale and work environment.